Traditional farmers’ pig trait preferences and awareness levels toward reproductive biotechnology application in Zambia - Abigaba, Rubaijaniza; Sianangama, Pharaoh Collins; Nyanga, Progress H; Mwenya, Wilson N M; Mwaanga, Edwell S (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study assessed traditional farmers’ preferences for indigenous pigs and their awareness levels toward reproductive biotechnology. Materials and Methods: This cross-sectional, descriptive study employed a mixed-methods concurrent triangulation design with a pragmatic approach. For quantitative data collection, a randomly selected sample size of 622 respondents was interviewed using a structured questionnaire. A semi-structured interview guide was used in seven focus group discussions (FGDs) for qualitative data. For quantitative data, descriptive statistics were used to find out how often something happened, and chi-square tests were used to look for relationships. For qualitative data, thematic analysis was used. Results: The majority (66.9%) of respondents were female, and they had largely (64.8%) attended a primary level of education. A slight majority (43.1%) of the respondents were 30–45 years old. Most respondents (65.1%) were low-income earners (below K500). Incidentally, the majority (74.1%) of respondents had low awareness of reproductive biotechnologies. Respondents’ awareness levels were associated with gender (p < 0.001), education (p < 0.001), income (p < 0.01), and not age (p > 0.05). With regard to trait preference, a total of seven indigenous pig traits were reportedly preferred, of which disease resistance (25.9%) and litter size (23.8%) were the most preferred. From FGDs, participants valued indigenous pigs, citing many preferred traits, of which disease resistance and litter size were the most emphasized traits. Some participants were aware of many reproductive biotechnologies and their perceived advantages. However, they were more familiar with artificial insemination, heat detection methods, and synchronization. Conclusions: The majority of respondents had low awareness of reproductive biotechnologies. Respondents’ awareness was associated with sociodemographic characteristics. The identified indigenous pig traits preferred by traditional farmers included adaptive and productive traits. J. Adv. Vet. Anim. Res., 9(2): 255–266, June 2022 http://doi.org/10.5455/javar.2022.i591